Proposta de VIM On-Demand para fatiamento de Nuvem - Zanela, Eduardo Henrique Rocha (2019)
The evolution of mobile communication is opening up opportunities for the innovation of vertical industries, whose varied applications demand different requirements. The insertion of 5G networks in vertical industries requires an infrastructure preparation to efficiently support numerous and varied services, one of the alternatives for this is the network slicing. Network slicing allows network operators to simultaneously provide a number of dedicated virtual networks with specific functionalities over a common network infrastructure, allowing a variety of services for different applications. This paper presents a proposal for a Virtualized Infrastructure Manager On-Demand for cloud slicing that allows bare metal control and network services with focus in on-demand creation. For this, a management system was implemented using Openstack in conjunction with virtualization tools allowing the instantiation of a physical machine. In this paper, we present 3 options of installation: complete instantiation bare metal, complete instantiation with containers and complete instantiation with preloaded image. The results indicate that the proposed, implemented, orchestrated and tested architecture meets the requirements of VIM On-Demand, and points out the main prevailing points in VIM.